Geometric influence of the laser-based powder bed fusion process in Ti6AL4V and AlSi10Mg - Chua, Zhong Yang (2021)
Many studies have shown that the mechanical properties and geometric accuracy of additive manufacturing parts are dependent of many factors such as laser energy density, build orientation, and heat transfer histories. Amongst the factors, heat transfer histories are highly dependent on the geometry of a part, resulting in influencing the mechanical properties and microstructure evolution due to the repeated heating and cooling process. Heat transfer histories are associated with material thermal properties which include thermal conductivity, thermal diffusivity, specific heat capacity, and temperature gradient. The objective of this paper is to understand and observe the microstructure evolution process and microhardness based on variation in geometrical characteristic of the laser-based powder bed fusion (L-PBF). This paper presents the effect of the geometric factors on the mechanical properties and geometric accuracy during the L-PBF process, which benefit future process optimisation and modelling. In this study, samples with varying wall thickness are fabricated in TI6AL4Vand AlSi10Mg alloys by L-PBF. The samples are systematically evaluated by the optical microscope and the Vickers hardness tester. Microstructural characterisation of these samples is further evaluated via scanning electron microscopy. The results show that there is a signification relationship between material thermal properties, microstructure evolution, and mechanical properties with respect to the variation in wall thickness. These results can be used to understand the material thermal behaviour in lattice structures with a thin or small-sized feature and serve as a design guideline to indirectly control the microstructure of a L-PBF part.